2021
DOI: 10.3389/fphar.2020.616813
|View full text |Cite
|
Sign up to set email alerts
|

AMPK/SIRT1 Pathway is Involved in Arctigenin-Mediated Protective Effects Against Myocardial Ischemia-Reperfusion Injury

Abstract: Arctigenin, one of the active ingredients extracted from Great Burdock (Arctium lappa) Achene, has been found to relieve myocardial infarction injury. However, the specific mechanism of Arctigenin against myocardial infarction remains largely unknown. Here, both acute myocardial ischemia-reperfusion injury (AMI/R) rat model and oxygen glucose deprivation (OGD)-induced myocardial cell injury model were constructed to explore the underlying role of AMPK/SIRT1 pathway in Arctigenin-mediated effects. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Several studies have reported the antioxidant and anti-inflammatory activities of arctigenin in different pathologies. In cerebral and myocardial ischemia, the same mode of action of arctigenin has been reported, through activation of SIRT1 signaling pathway [ 242 , 244 ]. From in vivo studies of myocardial ischemia, arctigenin seemed to activate AMPK/SIRT1 signaling pathway, and consequently an upregulation of I-κB and inhibition of NF-κB have been observed.…”
Section: Epigenetic Modulator Capacity Of Dietary Phytoestrogensmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies have reported the antioxidant and anti-inflammatory activities of arctigenin in different pathologies. In cerebral and myocardial ischemia, the same mode of action of arctigenin has been reported, through activation of SIRT1 signaling pathway [ 242 , 244 ]. From in vivo studies of myocardial ischemia, arctigenin seemed to activate AMPK/SIRT1 signaling pathway, and consequently an upregulation of I-κB and inhibition of NF-κB have been observed.…”
Section: Epigenetic Modulator Capacity Of Dietary Phytoestrogensmentioning
confidence: 80%
“…From in vivo studies of myocardial ischemia, arctigenin seemed to activate AMPK/SIRT1 signaling pathway, and consequently an upregulation of I-κB and inhibition of NF-κB have been observed. Thereby, it has been able to reduce oxidative stress, inflammation and apoptosis in cardiomyocytes, through SIRT1 signaling pathways [ 244 ]. Moreover, in vivo and in vitro experiments have demonstrated that arctigenin treatment effectively inhibited cerebral ischemia, by inducing NLRP3 inflammasome activation and IL-1β, IL-18 secretion and by activation SIRT1 [ 242 ].…”
Section: Epigenetic Modulator Capacity Of Dietary Phytoestrogensmentioning
confidence: 99%
“…In the present study, the expression of the members of the sirtuin family of proteins (Sirt1–7) revealed that only Sirt1 was significantly elevated by MLN4924 pretreatment in MI/R mice in vivo . Excitingly, Sirt1 has important physiological and pathological significance in cardiovascular diseases, especially for MI/R [ 45 ]. Studies have found that Sirt1 can exert cardioprotection by influencing cellular autophagy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of PALI, the uncontrollable hepatic inflammatory response and elevated oxidative stress triggered by SAP will continue to damage hepatocytes, which are central mediators for accelerating the development of PALI ( Yang et al, 2003 ; Moniaux et al, 2011 ). According to previous reports, AMPK activation is involved in the inhibition of the IL-6-stimulated inflammatory response in human liver cells and mediates the antioxidant stress ability of fibroblast growth factor (FGF) one in a mouse model of nonalcoholic fatty liver disease ( Nerstedt et al, 2013 ; Liu et al, 2020 ). Therefore, we explored the hypothesis that the molecular basis of AICAR in improving PALI is attributed to its anti-inflammatory capability and reduction of hepatic oxidative stress by AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, AMPK is activated under energy stress by sensing an increase in the ratios of AMP/ATP and ADP/ATP, thereby stimulating the catabolic process and maintaining energy homeostasis ( Lin and Hardie, 2018 ). In addition to its role in energy dynamic balance, activated AMPK is also associated with reducing redox stress, inhibiting inflammation or limiting cell proliferation ( Zimmermann et al, 2015 ; Liu et al, 2020 ; Chin et al, 2021 ). Recent studies indicate that AMPK activation plays an inhibitory role in mediating ethanol-induced oxidative stress in human pancreatic acinar cells, whereas AMPK inhibition can aggravate liver inflammation in mice with hepatic ischemia-reperfusion ( Zhou et al, 2018 ; Srinivasan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%